IMPLEMENTASI METODE PROTOTYPE DALAM PENGEMBANGAN WEBSITE SOLO RADIO MENGGUNAKAN APLIKASI CMS WORDPRESS - Hartanto, Hana Violetta; Purnamasari, Kartika Prasetya (Jurnal Industri Kreatif dan Inovatif, 2024)
Website development is an important part for maintaining the life and competiveness of an organization, including in the radio industry. Because Solo Radio is one of the famous radio stations in the city of Solo, an accurate and informative digital website is needed.. The purpose of this study is to implement a prototype method that conducts website development for Solo Radio using a WordPress Content Management System. The prototype method was chosen because it involves people directly in the production process, and the development process can be improved many times after they get their input.. The development process of this method started from gathering the user requirements, which was followed by the creation and evaluation of prototypes that lead to hundreds of iterations. Consequently, the prototype could be further developed into the final product people expected. The results of this study can be drawn on several aspects, in particular, website should have a good quality in both functional and aesthetic values. Therefore, a smooth user experience would be subjective depending on user's perspective of good user experience in website. In addition, WordPress was a website CMS with flexible and easily-managed features for content in the development of a Solo Radio website. The conclusion of this study suggests that the collaboration between developer and user will impact on the quality of a website while the selection of technology wesbite also could determine the quaility of website a company having.